Novel vasocontractile role of the P2Y14receptor: characterization of its signalling in porcine isolated pancreatic arteries - Alsaqati, M.; Latif, M.L.; Chan, S.L.F.; Ralevic, V. (Wiley, 2014)
Background and Purpose: The P2Y14 receptor is the newest member of the P2Y receptor family; it is Gi/o protein-coupled and is activated by UDP and selectively by UDP-glucose and MRS2690 (2-thiouridine-5′-diphosphoglucose) (7–10-fold more potent than UDP-glucose). This study investigated whether P2Y14 receptors were functionally expressed in porcine isolated pancreatic arteries. Experimental Approach: Pancreatic arteries were prepared for isometric tension recording and UDP-glucose, UDP and MRS2690 were applied cumulatively after preconstriction with U46619, a TxA2 mimetic. Levels of phosphorylated myosin light chain 2 (MLC2) were assessed with Western blotting. cAMP concentrations were assessed using a competitive enzyme immunoassay kit. Key Results: Concentration-dependent contractions with a rank order of potency of MRS2690 (10-fold) > UDP-glucose ≥ UDP were recorded. These contractions were reduced by PPTN {4-[4-(piperidin-4-yl)phenyl]-7-[4-(trifluoromethyl)phenyl]-2-naphthoic acid}, a selective antagonist of P2Y14 receptors, which did not affect responses to UTP. Contraction to UDP-glucose was not affected by MRS2578, a P2Y6 receptor selective antagonist. Raising cAMP levels and forskolin, in the presence of U46619, enhanced contractions to UDP-glucose. In addition, UDP-glucose and MRS2690 inhibited forskolin-stimulated cAMP levels. Removal of the endothelium and inhibition of endothelium-derived contractile agents (TxA2, PGF2α and endothelin-1) inhibited contractions to UDP glucose. Y-27632, nifedipine and thapsigargin also reduced contractions to the agonists. UDP-glucose and MRS2690 increased MLC2 phosphorylation, which was blocked by PPTN. Conclusions and Implications: P2Y14 receptors play a novel vasocontractile role in porcine pancreatic arteries, mediating contraction via cAMP-dependent mechanisms, elevation of intracellular Ca2+ levels, activation of RhoA/ROCK signalling and MLC2, along with release of TxA2, PGF2α and endothelin-1.